TINJAUAN LITERATUR INDIKATOR KINERJA BERBASIS PERINGKAT DALAM EVALUASI JARINGAN SELULER 4G LTE - Lin Fitri Alif Aisyah; Muhammad Putra Pamungkas; Sri Yusnita; Yulindon Khaidir (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
This study presents a literature review on ranking-based performance indicators in the evaluation of 4G LTE cellular networks. Conventional network performance evaluation commonly relies on Key Performance Indicators (KPIs) such as throughput, latency, and packet loss, which are typically assessed using average values. However, this approach often fails to represent the performance experienced by users under worst network conditions. Therefore, this study aims to analyze and highlight the role of ranking-based KPIs, particularly Rank2%, in providing a more representative evaluation of network performance. The research employs a structured literature review method by analyzing relevant journal articles from reputable databases published in recent years. The results show that ranking-based KPIs are more sensitive in capturing extreme conditions, especially for users experiencing the lowest quality of service. In addition, these indicators are closely related to Quality of Experience (QoE), as they better reflect user-perceived performance. This study concludes that integrating ranking-based KPIs with conventional metrics can improve the accuracy and effectiveness of LTE network performance evaluation.